Application of Hyperspectral imaging to predict the pH, intramuscular fatty acid content and composition of lamb M. longissimus lumborum at 24 h post mortem. (October 2017) - Craigie, C.R.; Johnson, P.L.; Shorten, P.R.; Charteris, A.; Maclennan, G.; Tate, M.L.; Agnew, M.P.; Taukiri, K.R.; Stuart, A.D.; Reis, M.M.
Abstract: Cost-effective, rapid and objective measurement of lamb quality on a routine basis is an important step for lamb value chains wishing to manage lamb product quality. Hyperspectral imaging (HSI) technology has shown promise as a solution for objective non-invasive prediction of meat quality. The performance of HSI applied 24 h post mortem to lamb M . longissimus lumborum (LL) within a processing plant environment was assessed over two sampling years to evaluate its suitability for an objective lamb meat quality assurance tool. Calibration and validation steps were undertaken to evaluate HSI prediction performance for predicting fatty acid content and composition (n = 1020 lambs) and pH (n = 2406 lambs). Practical considerations of reference meat quality data quality and validation strategies are discussed. HSI can be used to predict meat quality parameters of lamb LL with varying accuracy levels, but ongoing calibration and validation across seasons is required to improve robustness of HSI for objective non-invasive assessment of lamb meat quality. Highlights: Hyperspectral Imaging at 24 h post mortem can predict lamb meat quality. Quality traits included intramuscular fat content, composition and pH of the loin. Validation of performance across time is important for industrial uptake of technology. Hyperspectral imaging shows promise for objective lamb meat quality assurance.